(untitled) (European Journal of Pure and Applied Mathematics, 2024)
Different integral transforms have extensive applications in the various areas of science and engineering. Some of the new integral transforms of extended k-generalized Mittag-Leffler function are discussed in this paper. We examine integral transforms such as the Euler-Beta, Laplace, Mohand, Aboodh, SEE, and Sadik transform. Moreover, we also tried to establish the graphical representations of these transforms.